Three-dimensional anatomy of the Denonvilliers’ fascia after micro-CT reconstruction - Seung Yoon Yang (Nature Portfolio, 2021)
Abstract An understanding of the anatomy of the Denonvilliers’ fascia is essential for successful surgical outcomes for patients with rectal cancer in the mid- to lower regions, especially near the seminal vesicles and prostate in males. Whether the correct surgical plane during a total mesorectal excision should be anterior or posterior to the Denonvilliers’ fascia is currently under debate. This study aimed to investigate the Denonvilliers’ fascia using micro-computed tomography (micro-CT) to acquire three-dimensional images nondestructively for assessments of the relationship between the Denonvilliers’ fascia, the mesorectal fascia, and neurovascular bundles to elucidate the correct anterior total mesorectal excision plane. Eight specimens were obtained bilaterally from four fresh human cadavers. Four specimens were stained with phosphotungstic acid to visualize the soft tissue, and micro-CT images were obtained; the other four specimens were stained with Masson’s trichrome to visualize connective tissue. Micro-CT images corroborate that the Denonvilliers’ fascia consists of a multilayered structure that separates the rectum from the seminal vesicles and the prostate. Specimens stained with Masson’s trichrome showed that the urogenital neurovascular bundle located at the posterolateral corner of the prostate is separated from the mesorectum by the Denonvilliers’ fascia. For the preservation of autonomic nerves necessary for urogenital function and optimal oncologic outcomes in patients with rectal cancer, a successful mesorectal excision requires a dissection plane posterior to the Denonvilliers’ fascia.